Implementation of Village Minister Regulation No. 21 of 2015 in Utilization of Village Funds for Community Empowerment (Study in The Village of Embacang Kelekar and Suban Baru Village of Kelekar District in 2016) - Kendi, Sumar; Alfatih, Andy (HM Publisher, 2019)
This research is about the Implementation of Village Ministerial Regulation, PDTT Number 21 of 2015 in the utilization of Village Funds for Community Empowerment in Embacang Kelekar Village and Suban Baru Village Kelekar District of Muara Enim Regency in 2016. The research aims to find out the implementation of Village Ministerial Regulation, PDTT Number 21 of 2015 in utilizing village funds for community empowerment in Embacang Kelekar Village and Suban Baru Village Kelekar District Muara Enim Regency in 2016 and what factors are the obstacles to the success of the Implementation of the Village Minister Regulation, PDTT No. 21 2015 in Utilizing Village Funds for Community Empowerment in both villages. This study uses qualitative research methods with a descriptive approach. The data used are primary data and secondary data. The results of this study, in terms of the many developing programs, of course the government of Embacang Kelekar Village is better than Suban Baru Village because in Embacang Kelekar Village out of 8 groups of goat management only 2 groups failed and 6 other groups succeeded. Whereas in Suban Baru Village, out of 3 programs, only 1 group developed and the rest failed. This indicates that the impact in Embacang Kelekar Village is better than in Suban Baru Village. However, as a whole, when viewed from compliance and smooth routines, functions such as supervision are still not good in both villages. Therefore, when referring to the theory that is used as a reference, namely Ripley and Franklin's Theory, which states that even though the level of compliance is high, routine functions can be carried out smoothly, policy implementation can have a positive impact. However, if one of the three dimensions is flawed, the implementation of the policy is said to have yet to succeed. So the conclusion that can be drawn is the implementation of the Minister of Village Regulation, PDTT No. 21 of 2015 in the utilization of village funds for community empowerment in the Village of Embacang Kelekar and Suban Baru Village Kelekar District of Muara Enim Regency in 2016 can still be said to be unsuccessful.